A MALE WITH GRAVES’ DISEASE AND PAPILLARY THYROID CANCER WITHIN A THYROGLOSSAL DUCT CYST - Logwin, Sergio; Bueno, Elvio; Romero, Fabiola; Jimenez, Violeta; Ruiz, Daisy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Malignancy within a thyroglossal duct cyst is infrequent, accounting for only 0.7 to 1% of thyroglossal duct cysts. It predominantly occurs in women. Majority are euthyroid, though some may have associated Hashimoto's thyroiditis. CASE A 42-year-old male presented with a 5-year history of a large anterior neck mass. He was previously diagnosed with Graves' disease and thyroid orbitopathy. Neck ultrasound showed a right submandibular mixed tumor measuring 36 x 30 mm with nonspecific lateral cervical lymph nodes and multiple mixed oval images with well-defined borders measuring less than 13 mm in diameter. He has moderate quiescent orbitopathy on ophthalmologic exam. He received treatment with high doses of methimazole and lithium carbonate for severe hyperthyroidism with difficult stabilization. Sistrunk surgery and total thyroidectomy were eventually performed. Histology report showed a 1.5 cm papillary thyroid carcinoma within a thyroglossal duct cyst. In the literature we reviewed, there has been no other case involving a papillary thyroid carcinoma in a thyroglossal cyst with concomitant Graves' disease. Due to the low frequency of papillary thyroid carcinoma in a thyroglossal duct cyst, consensus has not been reached regarding the most appropriate treatment and follow- up. The management approach is currently based on the existing guidelines for differentiated thyroid cancer, with Sistrunk surgery and total thyroidectomy as the most appropriate initial treatment.